2017
DOI: 10.1177/2050157917708329
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Internet access and use: Extending the digital divide and usage gap

Abstract: This study uses survey data from the Pew Internet and American Life Project to advance digital divide research by exploring how smartphone dependence—in which one’s only means of accessing the Internet is via a smartphone—and smartphone use differ between key demographic groups in the United States. Results show differences in smartphone dependence and use based on race, age, income, and education. Minority group members, younger, lower income, and less educated users are more likely to be smartphone-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
137
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(148 citation statements)
references
References 35 publications
8
137
0
3
Order By: Relevance
“…It also comes with physical limitations, for example regarding screen size and keyboard usability. Thus, complex but beneficial tasks such as editing text documents and tables (e.g., Google Docs, Google Sheets) are much harder to do on a mobile device (Gitau, Marsden, & Donner, ; Tsetsi & Rains, ). Accordingly, mobile Internet access is described as extractive, rather than immersive (Humphreys, Von Pape, & Karnowski, ), centered on seemingly more superficial use modalities such as browsing, entertainment, and socializing.…”
Section: First‐level Digital Dividementioning
confidence: 99%
“…It also comes with physical limitations, for example regarding screen size and keyboard usability. Thus, complex but beneficial tasks such as editing text documents and tables (e.g., Google Docs, Google Sheets) are much harder to do on a mobile device (Gitau, Marsden, & Donner, ; Tsetsi & Rains, ). Accordingly, mobile Internet access is described as extractive, rather than immersive (Humphreys, Von Pape, & Karnowski, ), centered on seemingly more superficial use modalities such as browsing, entertainment, and socializing.…”
Section: First‐level Digital Dividementioning
confidence: 99%
“…One key difference is in functionality, where complex tasks are more difficult to accomplish on mobile devices (Donner et al, 2011;Tsetsi and Rains, 2017;Wang and Liu, 2017;Wyche et al, 2018). Usability studies conducted in the developing world have shown that mobile phones are functionally difficult to use (Gitau et al, 2010;Medhi et al, 2011).…”
Section: Theoretical Background: the Mobile Underclassmentioning
confidence: 99%
“…44,45 Although all participants in this study did have access to the internet, the true reflection of individuals that have access in these communities may not be represented. Access to the internet was an advertised requirement for participation in this project.…”
mentioning
confidence: 98%
“…Future programs incorporating UGC videos may not need to incorporate the cost of providing cameras to participants (even when working with low income communities). 45,48 Although many participants had internet access at home and download speeds were not a reported barrier, upload speeds were found to vary. Limited upload speeds were found to be a barrier to uploading videos for many families.…”
mentioning
confidence: 99%
See 1 more Smart Citation